Pengembangan Soal Numerasi Berbasis Wordwall Pada Konten Aljabar - Fadhilah, Lailafi (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2024)
This research aims at the development of wordwall-based numeracy questions on algebra content. Numeracy is one of the provisions in the independent curriculum which is currently widely applied in schools. Students' ability to solve numeracy problems can be known by using evaluation tools. Wordwall is one form of innovation that can be used as an evaluation tool. Wordwall itself can be accessed via laptop or smartphone. The type of research used in this study is a type of development research with the Plomp model. This study used 33 students as research subjects. The results of this development research are in the form of wordwall-based numeracy question products that are tested very valid (97%), very practical (86.29%) and effective (88%). The resulting product is in the form of 20 numeracy questions